Effectiveness measurement: when will we get it right? - Dwyer, Rocky J. (Universidad ESAN. ESAN Ediciones, 2009)
Credible demonstration of policy or program impacts depends on understanding the distinction between inputs outputs outcomes and indicators. Moreover in order to be trusted public reports on a programs' performance need to focus more selectively on identifying the key measures of performance. In the first place the aim of the article is to provide those involved in the practice of program evaluation with enhanced understanding of the current literature reports and documentation on estimating impacts and results of government programs and policies. Secondly it is designed to share definitions and guidelines used to determine economic impacts. Finally this article includes current best practices involved in measuring incremental impacts all of which we contend enable program evaluation staff providing them with new ways of approaching measurement effectiveness and accountability in a strategic and comprehensive manner.

Una demostración confiable sobre el impacto de políticas o programas depende de la comprensión de la diferencia entre lo que son aportes rendimientos resultados e indicadores. Es más para que los informes públicos sobre el desempeño de los programas sean confiables necesitan enfocarse de manera más selectiva o identificar las pautas claves de su actuación. En primer lugar el objetivo de este artículo es proveer a aquellos que están involucrados en la práctica de evaluación de programas de un mayor entendimiento de la literatura disponible en este momento así como informes y documentación para estimar los impactos y resultados de los programas y políticas de gobierno. En segundo lugar está redactado para compartir las definiciones y guías que se usan para determinar los impactos económicos. Finalmente este artículo incluye las mejores prácticas para calcular los incrementos en el impacto lo que argüimos habilita al personal evaluador de programas con nuevas aproximaciones a aspectos como mediciones efectividad y responsabilidad de gestión de una manera estratégica e integral.
Keywords: Accountability; Attribution; Effectiveness measurement; Responsabilidad de gestión; Performance measurement; Atribución; Medición de efectividad; Program evaluation; Medición de desempeño; Results-oriented measurement; Evaluación de programa; Medición por resultados; Managing for results; Gerencia por resultados; https://purl.org/pe-repo/ocde/ford#5.02.04